Eksistensi Ritual Tabuh Rah dalam Kehidupan Keagamaan Di Desa Dukuh Kecamatan Kubu Karangasem: (Perspektif Teologi Kebudayaan) - Putra, I Wayan Sunampan (Jayapangus Press, 2025)
Tabuh rah (traditional Balinese music) is a Balinese cultural tradition present in religious activities. Its development has sometimes undergone dynamics, but unlike in Dukuh village, tabuh rah still exists as a religious activity in yadnya ceremonies. To address this issue, a study was conducted aimed at analyzing tabuh rah from a cultural theology perspective. This is because tabuh rah, as part of Balinese culture, reflects a theological dimension. The research employed qualitative research, with data collection using observation, interviews, and documentation. The analysis revealed that tabuh rah exists for various reasons, including theological, sociological, and cultural reasons. Tabuh rah is typically performed during dewa yadnya and bhuta yadnya ceremonies. Tabuh rah, as a cultural practice with a theological dimension, demonstrates the concept of cultural theology. Based on this analysis, it can be concluded that Balinese culture is intertwined with theological aspects, thus presenting the concept of cultural theology. This cultural theology concept can certainly contribute to cultural preservation and strengthen theological understanding.